Bioethanol production from rice husk under elevated temperature simultaneous saccharification and fermentation using Kluyveromyces marxianus CK8 - Woottichai Nachaiwieng (2018)
© 2015 Elsevier Ltd. The thermotolerant yeast capable of ethanol fermentation at 45. °C, Kluyveromyces marxianus CK8, was used as the fermenting yeast incorporated with a commercial cellulolytic enzyme in the simultaneous saccharification and fermentation (SSF) on rice husk. Among seven factors screened through a Plackett-Burman design, four factors including substrate concentration, temperature, incubation period, and pH were found to be significantly influenced in the SSF process. After a 96. h fixed incubation period, the other three factors were analyzed for optimum conditions through a central composite design (CCD) and response surface methodology (RSM). The predicted maximum ethanol yield was 15.40. g/L obtained from 9.44% (w/. v) substrate concentration, 43. °C, and pH 4.2. The SSF experiment using the optimum condition predicted by the RSM model was investigated and an ethanol yield of 15.63. g/L was obtained, which was 101.5% of the predicted maximum value. Ethanol production yield increased 1.44 fold when compared with Separate Hydrolysis Fermentation (SHF). This is the first report described the influence factors and optimal condition for SSF process for ethanol production from rice husk celluloses at elevated temperature of 43. °C.